Opinions of owners and managers on the business risks of SMEs sustainability: does gender matter? - Dvorsky, Jan; Olah, Judit; Bednarz, Joanna; Hudakova, Maria (Journal of Business Economics and Management, 2023)
The aim of the article is the quantification of the effect size of business risks in the context of small and medium-sized enterprises’ (SMEs) sustainability according to gender. Data collection was carried out in the period 12/2022–01/2023 using the CAWI methodology. 1,090 owners and managers from the business environment of the SME segment participated in the research in the Visegrad group countries. Structural equation modelling (SEM) was implemented on the evaluation of the hypotheses of research. The statistical software IBM SPSS Statistics and AMOS vs. 28 were used in the data analytics. The management of business risks, just like market, financial and personnel risks, has a strong positive impact on the sustainable development of SMEs. Personnel risk management is the most important determinant which has a strong positive impact on the sustainable development of SMEs with male entrepreneurs. Financial risk management has a medium positive effect on the sustainable development of SMEs for female entrepreneurs. The research findings illustrate the important role for key individuals in national development and for strategic documents dealing with how to help the SME segment.